Randomized phase-III study of low-dose cytarabine and etoposide + /− all-trans retinoic acid in older unfit patients with NPM1-mutated acute myeloid leukemia - Schlenk, Richard Friedrich; Weber, D.; Krzykalla, J.; Kindler, T.; Wulf, G.; Hertenstein, B.; Salih, H. R.; Südhoff, T.; Krauter, J.; Martens, U.; Wessendorf, S.; Runde, V.; et al. (Scientific reports, 2023)
The aim of this randomized clinical trial was to evaluate the impact of all-trans retinoic acid (ATRA) in combination with non-intensive chemotherapy in older unfit patients (> 60 years) with newly diagnosed NPM1-mutated acute myeloid leukemia. Patients were randomized (1:1) to low-dose chemotherapy with or without open-label ATRA 45 mg/m2, days 8-28; the dose of ATRA was reduced to 45 mg/m2, days 8-10 and 15 mg/m2, days 11-28 after 75 patients due to toxicity. Up to 6 cycles of cytarabine 20 mg/day s.c., bid, days 1-7 and etoposide 100 mg/day, p.o. or i.v., days 1-3 with (ATRA) or without ATRA (CONTROL) were intended. The primary endpoint was overall survival (OS). Between May 2011 and September 2016, 144 patients (median age, 77 years; range, 64-92 years) were randomized (72, CONTROL; 72, ATRA). Baseline characteristics were balanced between the two study arms. The median number of treatment cycles was 2 in ATRA and 2.5 in CONTROL. OS was significantly shorter in the ATRA compared to the CONTROL arm (p = 0.023; median OS: 5 months versus 9.2 months, 2-years OS rate: 7% versus 10%, respectively). Rates of CR/CRi were not different between treatment arms; infections were more common in ATRA beyond treatment cycle one. The addition of ATRA to low-dose cytarabine plus etoposide in an older, unfit patient population was not beneficial, but rather led to an inferior outcome.
Online veröffentlicht: 08. September 2023
Gesehen am 08.12.2023